Correlates of disappointment in a relationship of generations X, Y, Z: behavioural inhibition/activation system and sense of coherence - Monika Baryła-Matejczuk; Małgorzata Artymiak; Marta Pawelec (Journal of Modern Science)
Objectives The issue of mutual references, relationships and their quality is the centre of studies dealing with marriage and family. Fertility decline, increased number of divorces, increased expectations related to interpersonal relationships and at the same time a decline in the ability to establish and maintain such have been observed over the years by experts in various disciplines. Numerous attempts are made to define aspects of a successful relationship as one of the criteria for a fulfilling life. This study aims to explore the correlates of disappointment in a relationship among people from different generations (X, Y and Z).